250 POST-PERICARDIOTOMY SINDROME: A DESCRIPTIVE ANALYSIS OF A NEGLECTED SYNDROME. (15th December 2022) - Pili, Gianluca; Cianfanelli, Lorenzo; Maranta, Francesco; Rizza, Vincenzo; Castiglioni, Alessandro; De Bonis, Michele; Cianflone, Domenico
Abstract: Background: Post-pericardiotomy syndrome (PPS) is a condition in which the surgical incision of the pericardium provokes the onset of pericardial and/or pleural effusion as a result of the inflammatory response inside the pericardial and/or the pleural space. PPS is a common complication following cardiac surgery (CS) and it has a significant impact on post-surgical patients' management. Thus, it would be useful to find predictors in order to stratify patients in terms of risk of PPS and define tailored Cardiovascular Rehabilitation (CR) programmes. Purpose: The aim of this study was to assess the incidence and to elucidate the features of PPS in a population of patients undergoing cardiac surgery. Secondly, the study was focused on the findings of likeable predictors of PPS and PPS' relapse. Methods: A prospective cohort study was performed on 156 patients who underwent cardiac surgery and then were admitted to the CR Unit of our institute. Among the 156-patients population, 26 patients developed post-pericardiotomy syndrome. Pre-operative and post-operative anamnestic and clinical data were collected to define the baseline characteristics of the population. The predictive role of anamnestic data, type of surgical procedure and laboratory parameters was evaluated. Treatment was then started in the PPS population, analysed and compared to the outcome. Data were collected during CR hospital stay and after discharge, during follow up check-ups. During CR hospital stay, the analysis regarded first and second line medical therapy, which was started in case of persistence, worsening or relapse of the pericardial and/or pleural effusion. After discharge, the analysis considered the outcome of the therapy at a defined deadline. Binary logistic regression analysis was performed to identify possible predictors of PPS and PPS' relapse. All the variables with a univariate p-value <0.150 or clinically relevant were entered into the multivariate model. Results: The population comprehends 156 patients. PPS patients presented with pleural effusion pre surgical intervention in 3 cases (11.5% vs 0%; p-value < 0.001) and showed more frequently pericardial effusion early after surgery (53.8% vs 8.5%; p-value < 0.001). In 3 patients (1.9%) drainage of pleural effusion was needed (7.7% vs 0.8%, p-value= 0.019). At admission in the CR Unit 26 patients (16.6%) presented or subsequently developed PPS. Pericardial effusion was classified as mild in 18 patients (69.2%), moderate in 7 patients (26.9%) and severe in 1 patient (3.8%); the median value of pericardial effusion at diagnosis was 7.5 mm, while the median value of the maximum pericardial effusion was 9.5 mm. During in-hospital stay, a first line medical therapy was administered to 26 PPS patients (100%): 13 patients (50%) needed a switch to a second line therapy, 4 patients (15.4%) needed invasive treatment of the effusion, 3 patients (11.5%) needed percutaneous pleural drainage and 2 patients (7.7%) needed percutaneous pericardial drainage. Medical therapy' collateral effects occurred in 7 patients (26.95%). PPS therapy at discharge was administered to 22 patients (84.6%). At follow up, pericardial effusion occurred in 9 patients (36%), pleural effusion occurred in 3 patients (12%). Relapse of pleuro/pericardial effusion after therapy suspension occurred in 3 patients (12%) and consequently, pleuro/pericardial effusion resolution was obtained in 23 patients (92%). The median time of therapy interruption at follow up was 27 days (7–60). Binary logistic regression was performed to identify the clinical predictors of PPS and PPS' relapse, the multivariate analysis did not find statistical significance for independent predictors of both conditions. Conclusion: The PPS is a common complication of cardiac surgery. Further studies are needed to determine novel possible PPS predictors. Possible indicators of PPS relapse should be identified in patients with possible discontinuation of treatment.